The Effects of Herbicides Targeting Aromatic and Branched Chain Amino Acid Biosynthesis Support the Presence of Functional Pathways in Broomrape - Dor, Evgenia; Galili, Shmuel; Smirnov, Evgeny; Hacham, Yael; Amir, Rachel; Hershenhorn, Joseph (Frontiers in Plant Science, 2017)
It is not clear why herbicides targeting aromatic and branched chain amino acid biosynthesis successfully control broomrapes—obligate parasitic plants that obtain all of their nutritional requirements, including amino acids, from the host. Our objective was to reveal the mode of action of imazapic and glyphosate in controlling the broomrape Phelipanche aegyptiaca and clarify if this obligatory parasite has its own machinery for the amino acids biosynthesis. Phelipanche aegyptiaca callus was studied to exclude the indirect influence of the herbicides on the parasite through the host plant . Using HRT - tomato plants resistant to imidazalinone herbicides, it was shown that imazapic is translocated from the foliage of treated plants to broomrape attachments on its roots and controls the parasite. Both herbicides inhibited P. aegyptiaca callus growth and altered the free amino acid content. Blasting of Arabidopsis thaliana 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) and ALS cDNA against the genomic DNA of P. aegyptiaca yielded a single copy of each homolog in the latter, with about 78% and 75% similarity, respectively, to A. thaliana counterparts at the protein level. We also show for the first time that both EPSPS and ALS are active in P. aegyptiaca callus and flowering shoots and are inhibited by glyphosate and imazapic, respectively. Thus leading to deficiency of those amino acids in the parasite tissues and ultimately, death of the parasite, indicating the ability of P. aegyptiaca to synthesize branched-chain and aromatic amino acids through the activity of ALS and EPSPS, respectively.